ANALISIS STRATEGIS PADA RENCANA STRATEGIS PEMERINTAH KECAMATAN BETOAMBARI KOTA BAUBAU - Musi, Asis (JI@P, 2015)
Asis Musi, 2015. âAnalysis of the strategy of Batoambari Kota Baru SubdistrictGovernment strategic planâ. Slamet Riyadi University, Thesis, unpublished.The government of Betoambari Sub District as a Local Apparatus Work Unit ofBaubau City has devised some strategies poured into Renstra (Strategic Plan)of 2013-2018 to help to realize the vision of Baubau Mayor and to establishannual performance including strategic targets as specified in the achievementof target indicator specified in the annual performance stipulation ofBetoambari Sub District Government particularly in 2013 that in reality has notachieved the maximum target with the successfully gain category of 78.23%.For that reason, the measure taken to accomplish the strategic plan ofBetoambari Sub District government in the form of analysis on the BetoambariSub Districtâs strategic management-based Strategic Plan based on internaland external environment to identify strength, weakness, opportunity, andthreat of Betoambari Sub District government becomes a must to do as thedevelopment of alternative strategic issues in establishing the annualperformance strategy of Betoambari Sub District. The establishment of annualperformance strategy existing in Strategic Plan so far focused only on thestakeholdersâ perspective while the focus on internal analysis of businessprocess (the improvement of internal organization capacity) has not been themain indicator of performance. The objective of research was to analyze thestrategic plan of Betoambari Sub District of Bau-bau City. The theoryemployed was Brysonâs theory on strategic planning fro social organization,while the technique of analysis employed in this research was Wahyudiâsmatrix SWOT analysis concerning the combination of matrix-cross strategy, tofind out and to establish the appropriate choice of strategy for determining theannual performance strategic target of Betoambari Sub District government.This research provided an alternative strategic formulation the government ofBetoambari Sub District can develop in determining the strategic target ofannual performance in strategic plan period: (1) intensifying the existingpotency, (2) preparing adequate Human Resource and infrastructure insupporting the achievement of governmental duties, (3) enacting the mentalcharacter building, discipline, job motivation, and employeesâ conception ontheir main duty and function, and (4) encouraging the communityâsability/participation and independency in contributing actively to thegovernmental organizing process.Keyword: Strategic plan, annual performance strategy, matrix-cross strategy.